2016
DOI: 10.1161/circresaha.115.307856
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Regulation of Epicardial Adipose Tissue and Myocardial Redox State by PPAR-γ/Adiponectin Signalling

Abstract: Rationale: Adiponectin has anti-inflammatory effects in experimental models, but its role in the regulation of myocardial redox state in humans is unknown. Although adiponectin is released from epicardial adipose tissue (EpAT), it is unclear whether it exerts any paracrine effects on the human myocardium.Objective: To explore the cross talk between EpAT-derived adiponectin and myocardial redox state in the human heart. phox from the cytosol to the membranes. Induction of O 2 − production in H9C2 cardiac myocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 44 publications
1
126
0
4
Order By: Relevance
“…Moreover, rapid atrial beating in pigs and permanent AF in humans are associated with the expression of several genes able to regulate AT accumulation in human and pig atrial myocardium, a phenomenon attributed to an insufficient supply of oxygen and nutriments (11). Another example of cross-talk between AT and the atrial myocardium comes from the observation that human EAT secretes adipokines that regulate the oxidative status of the atrial myocardium (56). EAT expansion also could be caused by nutrient excess in which epicardium becomes engorged with lipids resulting from the overwhelmed capacity of s.c. AT to clear excess triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rapid atrial beating in pigs and permanent AF in humans are associated with the expression of several genes able to regulate AT accumulation in human and pig atrial myocardium, a phenomenon attributed to an insufficient supply of oxygen and nutriments (11). Another example of cross-talk between AT and the atrial myocardium comes from the observation that human EAT secretes adipokines that regulate the oxidative status of the atrial myocardium (56). EAT expansion also could be caused by nutrient excess in which epicardium becomes engorged with lipids resulting from the overwhelmed capacity of s.c. AT to clear excess triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent study using human atrial tissue reported that EAT secreted adipokine influenced myocardial NADPH oxidase activity via endocrine or paracrine effects. 14 Further, this modulation was mutual, in that it was found that oxidation products (such as 4-hydroxynoneal) also regulated the expression of adiponectin in EAT. 14 However the role of other sources of ROS that are important in AF perpetuation e.g., from mitochondria, and how these are related to adipokine production remains to be elucidated.…”
Section: Molecular/ionic Mechanismsmentioning
confidence: 99%
“…14 Further, this modulation was mutual, in that it was found that oxidation products (such as 4-hydroxynoneal) also regulated the expression of adiponectin in EAT. 14 However the role of other sources of ROS that are important in AF perpetuation e.g., from mitochondria, and how these are related to adipokine production remains to be elucidated. It is now well understood that membrane ion channels, as well as intracellular Ca 2+ homeostasis are remodeled in both paroxysmal and persistent AF, and govern both the electrical properties atrial myocytes and fibroblasts, and also cell proliferation in the latter.…”
Section: Molecular/ionic Mechanismsmentioning
confidence: 99%
“…Recent evidence suggests that epicardial fat affects cardiac biology via the release of adipokines in a paracrine or endocrine manner [7]. Epicardial fat could also have a role in the pathophysiology of acute pericarditis (given its close anatomical affinity with the pericardium), although this hypothesis has never been explored.…”
mentioning
confidence: 99%